(untitled) (SCIENCE TIME JOURNAL, 2026)
The present study examines the neuropedagogical indicators of students in higher education institutions, focusing on cognitive, emotional, and behavioral dimensions. Drawing upon contemporary neuroscience and pedagogical theory, the research identifies and analyzes key neurobiological markers that influence learning outcomes, academic performance, and educational adaptation. The study employs an interdisciplinary framework integrating educational neuroscience, cognitive psychology, and applied pedagogy to investigate how neurophysiological parameters – including attention span, memory consolidation patterns, emotional regulation capacity, and executive function development – correlate with students’ academic achievement. Through empirical analysis of undergraduate populations across diverse disciplinary backgrounds, the research reveals significant interdependencies between neural plasticity indicators and pedagogical effectiveness. The findings demonstrate that students exhibiting optimized neuropedagogical profiles – characterized by robust working memory, adaptive stress responses, and metacognitive awareness – consistently achieve higher academic outcomes and demonstrate greater resilience to educational challenges. These results substantiate the imperative for neuroeducation-informed curricular design and personalized learning pathways in contemporary higher education.